1551 Improving Safety of Vascular Catheter Insertion in High-Risk Newborns through Standardized Teaching. (October 2012) - Lee, KS; Jefferies, A; Dunn, M
Abstract : Background: Umbilical and percutaneous central catheter placement in high-risk newborns are common NICU procedures with high complication rates, particularly when inserter experience varies. We developed, implemented and evaluated a standardized catheter insertion training program for NICU clinicians to improve patient safety. Methods: Seventy-one clinicians were surveyed to assess learning needs. Using the results, a program that included a manual, didactic seminars, self-study electronic module, pocket cards and low-fidelity simulation for practice and feedback was developed. Effectiveness was assessed with pre- and post-training multiple choice knowledge tests and Xray quiz focused on recognition and management of catheter malposition, plus a post-training simulation performance test. Malposition of catheters inserted in the NICU was the primary outcome. Results: Real-life practice and simulation were the highest rated teaching methods. Seventy-six clinicians completed at least one program component over 3 months. Post-training knowledge scores (65±11% vs 85±9%, n=65, mean±sd) and Xray scores(59±13% vs 69±16%, n=60) improved significantly compared to pre-training (p<0.01). Performance checklist score was 88±8%. Learner satisfaction was high. Catheter malposition rate decreased from 56% (n=292) to 36% (n=374) (p>0.05). Conclusions: A standardized training program resulted in improved knowledge and recognition of catheter malposition but not a significant decrease in malposition rate in the NICU.